ANALISIS LITERATURE REVIEW TERHADAP NILAI, SIKAP DAN TANGGUNG JAWAB DALAM PELAKSANAAN CITA-CITA WARGA NEGARA - Agung Laksono; Dinar Aulia; Didik Tri Setiyoko (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
The implementation of civic ideals is strongly influenced by an individual's values, attitudes, and responsibilities. However, various studies indicate that these three aspects have not been optimally developed in educational practices or social life. This study aims to analyze the role and interrelationship of civic values, attitudes, and responsibilities through a literature review. The sources reviewed include journal articles, books, and research reports related to civic education. The results indicate that civic values ​​serve as a moral foundation, attitudes determine an individual's inclination towards public issues, and responsibilities are reflected in social actions. The gap between understanding and concrete actions arises from the predominantly cognitive nature of civics learning, low social participation, and the influence of digital culture. This study emphasizes the need to strengthen character education, civic literacy, and public participation to support the achievement of civic ideals